Conhecimento tradicional sobre Plantas Alimentícias Não Convencionais – PANC, no semiárido brasileiro - Aurino, Ana Nery Batista (2023)
Eating is an act that requires nutritional balance and desirable sensory characteristics. Such characteristics are found in several plant species, some of which are culturally considered “invisible” because their potential is not widely known, especially those plants restricted to traditional groups. Among these species, Non-Conventional Food Plants (PANC) can be an option to vary the menu. Based on this context, we analyzed databases of ethnobotanical studies, carried out over ten years, on native species from the semi-arid region of Brazil used for human consumption by traditional communities of farmers. These studies were conducted by the research groups of the Ethnobiology Laboratory (LET) and the Laboratory of Ethnobiology and Environmental Sciences (LECA), both of the Federal University of Paraíba (UFPB). This research covered 9 municipalities and 10 communities, in three different mesoregions. The data were obtained through semi-structured interviews, in which the vernacular names of the cited species were recorded according to the citation of the informants. The data were organized in spreadsheets and analyzed from the perspective of quantifying the botanical families and species cited by the residents, in addition to evidencing their habits. The plant parts used by the communities and the forms of consumption and preparation were also recorded. The Jaccard similarity coefficient (J) was used to statically verify and compare the list of species mentioned in each municipality, as well as between the mesoregions, and the Informant Consensus Factor (ICF) was tested to verify the quality of the information. A total of 635 people were interviewed, 280 men and 355 women. Regarding the botanical families, 14 different families were mentioned, with emphasis on the families Anacardiaceae and Fabaceae. Thirty different species were cited, among which Sarcomphalus joazeiro (Mart.) Hauenschild (juazeiro), Sideroxylon obtusifolium (Roem. & Schult.) T.D.Penn. (quixaba), and Ximenia americana L. (ameixa) stood out, mentioned in almost all study areas. The J index had an average of 0.3283 for the municipalities and 0.3506 for the mesoregions, and the ICF had an average of 0.87. Regarding the forms of use, the fruit was the most used part, especially consumed “in natura”, the most prominent form, comprising 29 species, followed by the production of juices (6 species) and sweets and jellies (2 species). Spondias tuberosa Arruda (umbu) was the most versatile species. In general, it can be observed that, even within the same semi-arid region, but in different mesoregions, there is a certain degree of variability in the list of food species mentioned in the communities, indicating that there are several species with food potential, which can be verified by the considerable number of PANC used in different forms of preparation, using fruits, tubers and seeds, improving their sensorial characteristics for consumption, which was confirmed by the high consensus among the informants. PANC can be inserted into people’s daily lives, as they are already widely used by traditional communities of farmers; however, more studies should be conducted from the nutritional perspective of these foods.